2010
DOI: 10.1016/j.cell.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Proneurogenic, Neuroprotective Chemical

Abstract: Summary An in vivo screen was performed in search of chemicals capable of enhancing neuron formation in the hippocampus of adult mice. Eight of 1,000 small molecules tested enhanced neuron formation in the subgranular zone of the dentate gyrus. Among these was an aminopropyl carbazole, designated P7C3, endowed with favorable pharmacological properties. In vivo studies gave evidence that P7C3 exerts its pro-neurogenic activity by protecting newborn neurons from apoptosis. Mice missing the gene encoding neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
344
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 311 publications
(353 citation statements)
references
References 40 publications
6
344
2
1
Order By: Relevance
“…Interestingly, a recent study reported that dimebon had remarkable effects on hippocampal neurogenesis, at doses comparable to those used in the present study (Pieper et al, 2010). One-week treatment of rats with dimebon at a dose of 0.1 mkM/kg (0.32 mg/kg) increased the number of BrdU-positive cells in the dentate gyrus.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Interestingly, a recent study reported that dimebon had remarkable effects on hippocampal neurogenesis, at doses comparable to those used in the present study (Pieper et al, 2010). One-week treatment of rats with dimebon at a dose of 0.1 mkM/kg (0.32 mg/kg) increased the number of BrdU-positive cells in the dentate gyrus.…”
Section: Discussionsupporting
confidence: 64%
“…One-week treatment of rats with dimebon at a dose of 0.1 mkM/kg (0.32 mg/kg) increased the number of BrdU-positive cells in the dentate gyrus. Because activation of structural plasticity and neurogenesis in the hippocampus is well demonstrated to be implicated in the mechanisms of contextual and spatial learning (Epp et al, 2007;Yang et al, 2008;Li et al, 2010;Pieper et al, 2010), we suggest that this effect might be one of the potential mechanisms which underlie the memory enhancing action of dimebon observed in the current study. Further experiments are required to address the possible link between the mnemonic effects of dimebon and its properties as a proneurogenic compound.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Transgenic mice with NPAS3 mutation showed a behavioral phenotype with reduced memory, impaired social recognition and impaired sensorimotor gating [86], which are also characteristics of schizophrenic patients. These animals simultaneously had a reduced neurogenesis in the dentate gyrus [87]. Aminopropyl carbazole, which promotes neurogenesis by preventing apoptosis in the neurogenesis process, was able to increase neurogenesis and reversed the malformation of dentate gyrus in NPAS3 knock-out animals [86].…”
Section: Neurogenesis and Schizophreniamentioning
confidence: 95%